Structural Vulnerability Analysis of Partially Interdependent Networks: The Joint Influence of Interdependence and Local Worlds - Wang, Jiawei; Sun, Shiwen; Wang, Li; Xia, Chengyi (Frontiers in Physics, 2020)
Previous studies have verified that the local-world mechanism can greatly affect the structural properties and dynamical processes occurring on isolated complex networks; however, the impact of local-world mechanism on structural vulnerability of interdependent systems is still not efficiently explored. Therefore, in this study, the joint influence of interdependence and local worlds on attack vulnerability of interdependent networks is addressed. First, a partially interdependent system model is proposed, consisting of two networks which are dependent on each other with different types of interdependence preference. In particular, each network evolves according to the local-world model with an adjustable parameter to control the size of local worlds during network evolution. Next, the cascading failure process induced by intentional attack on high-degree nodes is presented. Then, the responses of interdependent systems after cascading failures are investigated through large quantities of numerical simulations. The results show that the emergence of local worlds during network evolution plays an important role in the structural vulnerability of both single and interdependent networks; that is, networks with larger size of local worlds are found to be more vulnerable against attacks. Moreover, interdependent links make the entire system much more fragile, especially when the networks are with max–max assortative interdependence and the strength is enhanced. These results are beneficial to the deep understanding of the intrinsic connection between attack robustness and underlying structure of large-scale interdependent systems.